Operation Mechanism of GaN-based Transistors Elucidated by Element-Specific X-ray Nanospectroscopy - Keiichi Omika (Nature Portfolio, 2018)
Abstract With the rapid depletion of communication-frequency resources, mainly due to the explosive spread of information communication devices for the internet of things, GaN-based high-frequency high-power transistors (GaN-HEMTs) have attracted considerable interest as one of the key devices that can operate in the high-frequency millimeter-wave band. However, GaN-HEMT operation is destabilized by current collapse phenomena arising from surface electron trapping (SET), which has not been fully understood thus far. Here, we conduct quantitative mechanistic studies on SET in GaN-HEMTs by applying element- and site-specific photoelectron nanospectroscopy to a GaN-HEMT device under operation. Our study reveals that SET is induced by a large local electric field. Furthermore, surface passivation using a SiN thin film is demonstrated to play a dual role: electric-field weakening and giving rise to chemical interactions that suppress SET. Our findings can contribute to the realization of high-capacity wireless communication systems based on GaN-HEMTs.